Witnessing Lot's Wife - Watson, Ariell (Lumen et Vita, 2015)
The literature surrounding the fate of Lot’s wife agrees that memory is dangerous business. Scholarly opinions diverge, however, regarding whether the danger of “looking back” arose from the pain of grief or from subversive disobedience of divine injunction. Were the angel’s words a warning or a command? This paper will examine the role of the pastoral caregiver in witnessing traumatic memory. Pastoral relationships are present to various forms of recollection, including flashbacks, the therapeutic process, and ritual. This creates a dynamic of dual spectatorship: the individual looks at her/his traumatic past, while the caregiver looks at her/him. This tableau mimics the Biblical scene in which Lot’s wife becomes petrified as she glances toward her burning home; like Lot, the caregiver stands further removed from the horror. For fear of sharing his wife’s fate, Lot continues his journey without ever turning to bear witness to this loss. Inasmuch as the pastoral caregiver works to bear witness, (s)he is vulnerable to “vicarious trauma.” Unlike Lot, who forged ahead despite Sodom and his wife both crumbling behind him, the caregiver risks glimpsing the apocalyptic scene in the process of attending to the petrified woman. This leads back to the questions posed above: was the fate of Lot’s wife nature or punishment—and how can the pastoral caregiver heed this cautionary tale? This paper will describe transgressive, masochistic, and healing modes of memory, drawing from the literatures of pastoral and trauma studies. The caregiver’s role will be examined with regard to each mode in order to assess the importance of witness and the risk of vicarious trauma.